Love, Beauty, Marital Satisfaction, and Family Relations: A Study on Young Adult and Middle-Age Couples - Matsumoto, Camila Desidério (2016)
The objectives of this study were to analyze the relationship between variables: love, beauty, marital satisfaction and family relationships incouples living in the city of São Paulo, Brazil. We investigated 200 subjects (50 couples of young adults and 50 middle-aged couples). The following instruments were used: questionnaire; Sternberg's Triangular Love Scale; Marital Satisfaction Scale; Family Adaptability and Cohesion Evaluation Scale Adaptability, Faces III and; Marital Conflict Scale. It was found that middle-aged couples had higher marital satisfaction rather than adults young couples. The subjects who considered their spouse as a beautiful person were more: marital satisfaction (r=0.424; p<0.001), intimacy (r=0.384; p<0.001), passion (r=0,372; p<0,001) and decision/commitment (r=0,337; p<0,001); felt more love for your spouse (r=0,371; p<0,001). This group of couples also showed greater family cohesion (r=0,387; p<0,001) and less family conflict (r=-0,342; p<0,001). We conclude that the favorable perception of beauty both itself and the spouse has a positive influence on marital and family relationships.Keywords: Love; Beauty; Marital satisfaction; Family; Marriage.